Women's Struggles Reflected in Radioactive (2019) Movie - Putri, Dean Ananda; Wahyuningsih, Titik (ITScience (Information Technology and Science), 2025)
This research aims to describe the struggle of women in the field of work as depicted in the Radioactive (2019) movie, focusing on the life of Marie Skolodowska Curie - a pioneering female scientist. This problem is important to analyze because the gender inequality, discrimination, and patriarchy dominates women in the field of work they good at. The experience of the main character in the film, Maria Sklodowska Curie is important in this article. She must compete with male scientist to get equal right in the field of work faced in a male-dominated field, where she was denied resources, recognition, and respect despite her groundbreaking contributions to science. This study uses a qualitative descriptive method. The theory used was Betty Friedan’s liberal feminist theory. The researcher analyze the gender inequality, discrimination that experienced by the main character and the character that Marie Sklodowska Curie has that reflect her as a feminist. As a result of the research, there were several gender inequalities committed by male characters at that time towards Marie Sklodowska Curie such as unequal access to research facilities lack of funding, etc. and two attitudes that reflect Marie Sklodowska as a feminist, such as brave and intelligence. Through her character she managed to become the first female scientist in the world.